The Impact of Recent Generic Drug Price Policies on Pharmaceutical Innovation: A Theoretical Rationale and Proposal of a Method Supporting Innovation in Areas of Unmet Medical Need - Pierre-Alexandre Dionne; Farzad Ali; Mendel Grobler (Journal of Health Economics and Outcomes Research)
New discoveries are a critical priority for the pharmaceutical industry. However, the use of fixed incremental cost-effectiveness (ICER) thresholds for health technology assessment (HTA) may compromise incentives to innovate and affect future treatment options. This paper highlights the impact of generic drug price policies on pharmaceutical innovation in the context of fixed ICER thresholds and proposes a new consideration for the cost-effectiveness analysis (CEA).